Computed Tomography Angiography Collateral Profile Is Directly Linked to Early Edema Progression Rate in Acute Ischemic Stroke. Issue 12 (December 2019) - Broocks, Gabriel; Kemmling, Andre; Meyer, Lukas; Nawabi, Jawed; Schön, Gerhard; Fiehler, Jens; Kniep, Helge; Hanning, Uta
Abstract : Background and Purpose—: Poor collateral flow is associated with poor clinical outcome in acute ischemic stroke and may indicate futile recanalization after successful thrombectomy. Pronounced early formation of cerebral ischemic edema may be the link between poor collateral status and declined functional outcome, but this relationship has not been investigated yet. We hypothesized that collateral status is associated with early lesion water uptake as quantitative marker for edema progression. Methods—: One hundred seventy-six patients with middle cerebral artery stroke who underwent mechanical thrombectomy were analyzed. Status of cerebral collateral circulation (collaterals status [CS]) was derived using an established 5-point scoring system in admission computed tomography angiography, and good collaterals were defined as CS 3 to 4. Ischemic brain edema dynamics were quantified using early edema progression rate (EPR). EPR was derived from quantitative lesion water uptake in admission computed tomography divided by time from symptom onset to imaging. Good clinical outcome was defined as modified Rankin Scale score 0 to 2 after 90 days. Results—: The median EPR was 1.4% per hour (interquartile range, 0.5–3.5%) in patients with good collaterals, which was lower than the median EPR in patients with poor collaterals of 5.8% per hour (interquartile range, 2.1–5.9%; P <0.0001). In multivariable regression analysis, lower CS was significantly and independently associated with higher EPR (1.6% EPR per 1-point CS; P =0.002). A higher EPR was associated with reduced likelihood of good clinical outcome: odds ratio 0.87; (95% CI, 0.76–0.99; P =0.03). Conclusions—: Patients with poor CS had significantly higher EPR, which was associated with worse clinical outcome. These patients might benefit from adjuvant antiedematous treatment. Abstract : Supplemental Digital Content is available in the text.